2007
DOI: 10.1088/0031-8949/76/6/011
|View full text |Cite
|
Sign up to set email alerts
|

Mass distributions for nuclear disintegration from fission to evaporation

Abstract: By a proper choice of the excitation energy per nucleon we analyze the mass distributions of the nuclear fragmentation at various excitation energies. Starting from low energies (between 0.1 and 1 MeV/nucleon) up to higher energies about 12 MeV/n, we classified the mass yield characteristics for heavy nuclei (A > 200) on the basis of Statistical Multifragmentation Model. The evaluation of fragment distribution with the excitation energy show that the present results exhibit the same trend as the experimental o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…In [11,15] we have shown that the surface term coefficient increases slightly with decreasing N/Z of the fragments, and the symmetry energy coefficient for primary hot fragments at the low-density freeze-out is significantly reduced. Finally, besides the existing and recent calculations [12,[17][18][19], the present results for isoscaling give additional confidence to the statistical multifragmentation model.…”
Section: Discussionsupporting
confidence: 82%
“…In [11,15] we have shown that the surface term coefficient increases slightly with decreasing N/Z of the fragments, and the symmetry energy coefficient for primary hot fragments at the low-density freeze-out is significantly reduced. Finally, besides the existing and recent calculations [12,[17][18][19], the present results for isoscaling give additional confidence to the statistical multifragmentation model.…”
Section: Discussionsupporting
confidence: 82%
“…For a comparison of the statistical approach with experimental data we refer the reader to Ref. [10], where it has been shown that the results we obtained on the basis of the present statistical model are in good agreement with existing theoretical and experimental data.…”
Section: Theoretical Calculations and Resultssupporting
confidence: 80%
“…The mass and charge distributions at various excitation energies exhibit very different and interesting behavior. In our previous paper [10], we demonstrated that the evolution of the mass yield distribution is determined by the excitation energy. In the excitation energy range for E * ≤ 1 MeV per nucleon, one may observe fission-like distributions, while in the region of 1-3 MeV per nucleon an inverted U-shaped distribution is observed.…”
Section: Introductionmentioning
confidence: 89%
“…These findings are consistent with fission and evaporation processes which was investigated in Refs. (Eren et al, 2007; for normal nuclei and in Ref. (Botvina et al, 2016) for hypernuclei.…”
Section: Methodsmentioning
confidence: 97%